Efeito dos protocolos de fortalecimento muscular e exercício aeróbico sobre a dor, força muscular e desempenho físico nos indivíduos com osteoartrite de joelho - Moreira, Vanessa Martins Pereira Silva (2020)
Introduction: For the treatment of individuals with knee osteoarthritis (KOA), the American College of Rheumatology recommends conservative modalities and, among them, are the muscle strengthening (MS) and aerobic exercise (AE) protocols. However, it is still uncertain in the literature as to which of these exercises is most effective for this population. In addition, psychological factors are also important to consider for KOA and how much they influence physical performance and symptom improvement is still uncertain. Objectives: To evaluate the effect of the MS and AE protocols on pain, muscle strength and physical performance in individuals with KOA, considering the influence of age, BMI, depressive symptoms and pain catastrophization. In addition, verify whether these psychological factors are correlated with physical performance, considering the influence of age, BMI and pain. Material and methods: Ninety-eight individuals were assessed before and after the intervention protocols by the measures: Visual Numerical Scale, Pain Pressure Pressure Threshold, Beck Depression Questionnaire, Catastrophic Thought Scale, Western Ontario and McMaster Universities Osteoarthritis Questionnaire (WOMAC), Isometric Force and Gait Speeds. Subjects were randomized to one of the following protocols. 1) MS protocol: It consisted of strengthening the abductor muscles of the hip, quadriceps and anterior tibialis, through 4 sets of 6 repetitions; 2) AE Protocol: It consisted of 40 minutes on an exercise bike, in which the individual should maintain the range of 50-70% of the maximum heart rate; 3) Control Protocol (CT): It consisted of education through a 60-minute booklet and lectures on OAJ characteristics and execution of part of the physiotherapeutic protocol for home performance. The protocols were applied over a period of 8 weeks, 3 times a week. Statistical analyzes were performed using the Generalized Equations test and the Multiple Linear Regression test. Results: It was found that both FM and AS produced a positive short-term effect on pain, muscle strength and physical performance, considering the influence of depressive symptoms and pain catastrophization. Furthermore, the FM protocol proved to be more effective than the AE and the CT. As for the relationship between psychological factors and physical performance, an association was observed between depressive symptoms and pain catastrophization with self-reported and objective physical performance. However, catastrophizing pain was the best predictor of poor physical performance. Conclusions: MS is the most effective protocol for improving the symptoms of individuals with KOA, considering the influence of depressive symptoms and pain catastrophization. In addition, catastrophizing pain is the psychological measure that best predicts self-reported physical performance and depressive symptoms and objective physical performance in individuals with KOA.